2011
DOI: 10.1029/2011jd016283
|View full text |Cite
|
Sign up to set email alerts
|

On the effect of dust particles on global cloud condensation nuclei and cloud droplet number

Abstract: [1] Aerosol-cloud interaction studies to date consider aerosol with a substantial fraction of soluble material as the sole source of cloud condensation nuclei (CCN). Emerging evidence suggests that mineral dust can act as good CCN through water adsorption onto the surface of particles. This study provides a first assessment of the contribution of insoluble dust to global CCN and cloud droplet number concentration (CDNC). Simulations are carried out with the NASA Global Modeling Initiative chemical transport mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
182
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(186 citation statements)
references
References 121 publications
(193 reference statements)
4
182
0
Order By: Relevance
“…This is in line with Twohy et al (2009), who also found that dust arriving at the Cape Verde Islands had acted as CCN in trade wind cumuli. It also agrees with Karydis et al (2011), who show that mineral dust particles contribute significantly to CCN number concentrations, particularly in outflow regions of deserts, which, as shown here, might extend at least as far as Barbados for the Sahara. Not all air masses originating from Africa carried continental particles in such large numbers.…”
Section: Discussion Of the Different Aerosol Typessupporting
confidence: 78%
See 1 more Smart Citation
“…This is in line with Twohy et al (2009), who also found that dust arriving at the Cape Verde Islands had acted as CCN in trade wind cumuli. It also agrees with Karydis et al (2011), who show that mineral dust particles contribute significantly to CCN number concentrations, particularly in outflow regions of deserts, which, as shown here, might extend at least as far as Barbados for the Sahara. Not all air masses originating from Africa carried continental particles in such large numbers.…”
Section: Discussion Of the Different Aerosol Typessupporting
confidence: 78%
“…Accumulation type aerosol was connected to long-range transport from the Sahara and Sahel region, where either mineral dust from the desert and/or biomass-burning particles from the Sahel were involved in raising the particle number concentrations in the accumulation mode. Although particles from both biomass burning and mineral dust are sometimes assumed to be of rather insoluble nature, they have been shown to contribute to CCN (Engelhart et al, 2012;Twohy et al, 2009;Karydis et al, 2011), and an increase in N CCN due to their presence was also observed in the present study.…”
Section: Discussionsupporting
confidence: 62%
“…The annually and spatially averaged occurrence frequency of NLLJs is similar in and the atmospheric circulation (e.g. Sokolik and Toon 1996;Rosenfeld et al 2001;Lohmann and Feichter 2005;Tompkins et al 2005;Karydis et al 2011;Schmechtig et al 2011). In addition to these climate effects, suspended dust aerosol decreases the air quality with adverse influences on human health (e.g.…”
Section: Introductionmentioning
confidence: 93%
“…Note that deriving monthly-mean CDNC from monthly-mean sizeresolved particle concentrations and monthly-mean particle composition fields does not account for temporal variations in aerosol properties. However, our approach and our choice of updraught velocities have been shown to provide a good approximation of mean CDNC (Fountoukis et al, 2007;Pringle et al, 2009;Karydis et al, 2011). As with many other aerosol activation schemes (e.g., Chen and Penner, 2005;Roelofs et al, 2006), the employed scheme does not account for droplet collision-coalescence (i.e.…”
Section: Treatment Of Aerosol Activation and Model Evaluationmentioning
confidence: 99%